EVALUATION OF MALANG CITY'S ENVIRONMENTAL QUALITY BASED ON IOT DATA USING MCDM - Junikhah, Allin; Zafirah, Yasmin (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Malang City is one of the major cities in East Java with a high population. Based on the IoT data on the correlation between the number of vehicles and air quality in Malang City, this study evaluated the environmental quality with several criteria, including humidity, temperature, dust particulates, CO2, CO, and noise. The criteria data were assessed through MCDM methods, namely MOORA and SAW. These methods are very effective in determining the condition of pollution-prone zones from the lowest to the highest environmental quality locations through the resulting ranking. Through the MOORA method, Point 1: Jl. Raya Tlogomas, Tanggul Mas is the area that has the lowest MOORA score with a value of -0.364 and SAW score with a value of 0,808, which indicates that the area has the least conducive environmental quality. This study provides vital information for the awareness of the community and related parties to minimize the health effects caused.